A Sense of Ireland: reflecting and refracting modernity in Irish culture. Issue 3 (3rd July 2018) - King, Linda
ABSTRACT: During February and March 1980, an ambitious six-week long, multi-disciplinary arts programme took over London. Launched at the height of "the Troubles", A Sense of Ireland was a "diplomatic mission" to foster better relationships between Ireland and Britain. This essay critiques the catalogue that accompanied the festival as an important example of Irish design modernism that synthesised the aesthetics of the European and American avant-garde with a contemporary political and cultural critique.